2022
DOI: 10.1111/bjh.18466
|View full text |Cite
|
Sign up to set email alerts
|

Germline ERCC excision repair 6 like 2 (ERCC6L2) mutations lead to impaired erythropoiesis and reshaping of the bone marrow microenvironment

Abstract: Summary Despite the inclusion of inherited myeloid malignancies as a separate entity in the World Health Organization Classification, many established predisposing loci continue to lack functional characterization. While germline mutations in the DNA repair factor ERCC excision repair 6 like 2 (ERCC6L2) give rise to bone marrow failure and acute myeloid leukaemia, their consequences on normal haematopoiesis remain unclear. To functionally characterise the dual impact of germline ERCC6L2 loss on human primary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, this study included the first investigation into the consequences of ERCC6L2 alterations on the stromal niche, revealing in enhanced osteogenesis and suppressed adipogenesis [21]. This microenvironment resembles what was founded in sporadic cases of AML, suggesting the existence of a BM niche particularly prone to malignant transformations in ERCC6L2 mutated patients [22].…”
Section: Germline Ercc6l2 Mutations and Diseasementioning
confidence: 70%
“…Furthermore, this study included the first investigation into the consequences of ERCC6L2 alterations on the stromal niche, revealing in enhanced osteogenesis and suppressed adipogenesis [21]. This microenvironment resembles what was founded in sporadic cases of AML, suggesting the existence of a BM niche particularly prone to malignant transformations in ERCC6L2 mutated patients [22].…”
Section: Germline Ercc6l2 Mutations and Diseasementioning
confidence: 70%
“…The importance of the BM niche was advocated in a recent study using both patient samples and ERCC6L2-silenced cells which suggested that biallelic ERCC6L2 mutations also affect the mesenchymal stromal cells, which are paramount for fibrogenesis. 14 A prototype for somatic rescue is described in SAMD9/9L -mutated MDS with a nonrandom loss of chromosome seven, which was identified in 61% of the patients in a recent study. 25 Our data demonstrates that identifying somatically TP53-mutated clones at the initial presentation is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first depiction of patients with defective ERCC6L2, altogether 37 cases with biallelic germline ERCC6L2 variants have been described in the literature (including 14 patients from Finland). [1][2][3][10][11][12][13][14][15] In prior studies among Finnish patients, all cases have been homozygous for the variant ERCC6L2(NM_020207.7): c.1424delT (p.Ile475ThrfsTer36, rs768081343). 8,10 Moreover, a twenty-times-higher minor allele frequency of the variant in the Finnish population compared to the rest of the Europeans 16 suggests an accumulation of ERCC6L2 disease due to genetic drift as recognized in Finnish disease heritage (FDH).…”
Section: Introductionmentioning
confidence: 99%
“…Upon treatment with radiotherapy, these patients showed a strikingly longer disease-free and overall survival than patients with wild-type ERCC6L2, indicating that ERCC6L2 loss may be clinically relevant (22). The most recent study described an impaired clonogenic capacity and erythroid differentiation in ERCC6L2-silenced HSPCs and a probable impact on mesenchymal stromal cells and their differentiation potential (23).…”
Section: Ercc6l2 Acts As Crucial Nonhomologous End Joining Factormentioning
confidence: 96%
“…The overall penetrance is high with an estimate of 94% with two asymptomatic homozygotes still being very young (Table 1). Cytopenia and/or overt BMF develop early at an average age of 14 years and were reported in 24 out of 36 patients (66%, range 2 to 47 years (n=24), Table 1) (7,11,18,19,23,25,27,28). The development of hematologic malignancies (MDS/AML) has been described in approximately 31% of ERCC6L2 germlinemutated patients at an average age of 35 years (range 2-59 years (n=12), Table 1) (7,19,24,(28)(29)(30).…”
Section: Ercc6l2 Acts As Crucial Nonhomologous End Joining Factormentioning
confidence: 99%